De "Proculi damnatione". Proculus of Marseilles and the consolidation of the Gallic Church in the early fifth century - Natal, David (’Ilu. Revista de Ciencias de las Religiones, 2012)
This article focuses on Proculus of Marseilles’ long episcopate (ca. 381-428 AD) in order to analyse this key moment for the construction of the Gallic Church. A further aim of this paper is to implement a methodological approach that allows a nuanced assessment of complex processes of institutional development.